2015
DOI: 10.1155/2015/704502
|View full text |Cite
|
Sign up to set email alerts
|

A Secure User Authentication Scheme against Smart-Card Loss Attack for Wireless Sensor Networks Using Symmetric Key Techniques

Abstract: User authentication in wireless sensor networks (WSNs) is a critical security issue due to their unattended and hostile deployment in the field. In order to protect the security of real-time data query from an external user, many two-factor (password and smartcard) user authentication schemes are proposed. However, most of them are insecure against various attacks. This paper summarizes attacks and security requirements for two-factor user authentication in WSNs. Based on security requirements, a user authenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 19 publications
0
21
0
Order By: Relevance
“…In 2015, Chen et al propound a highly efficient and secure algorithm which can counter SSCA. It is a two‐factor UA scheme with session key establishment suitable for WSN.…”
Section: Pertinent Workmentioning
confidence: 99%
“…In 2015, Chen et al propound a highly efficient and secure algorithm which can counter SSCA. It is a two‐factor UA scheme with session key establishment suitable for WSN.…”
Section: Pertinent Workmentioning
confidence: 99%
“…Chen et al [ 28 ] recently suggested a secure user authentication scheme for wireless sensor networks. They claimed that their scheme could withstand different types of attacks, such as smart card loss attacks [ 29 ], replay attacks [ 30 ], stolen verifier attacks [ 31 ], privileged-insider attacks [ 32 ], user impersonation attacks [ 33 ], password guessing attacks [ 34 ], etc.…”
Section: Introductionmentioning
confidence: 99%
“…After performing a security analysis of Chen et al’s scheme [ 28 ], however, we find that their scheme is still vulnerable to smart card loss attack, and is susceptible to denial of service attack, because it uses the incorrect verification method. In addition, we observe that their scheme cannot preserve user anonymity because user’s identity is in plaintext form in login request message.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations